Teacher modes of adaptation to innovations in social studies - Malicdem, Melanio Doria 1936- (1986)
This study aims to determine the teacher modes of adaptation to innovations in the secondary social studies education; to appraise the influence of social acceptance values to such modes of adaptation; to assess the teacher's facilitative characteristics towards the said innovations; to compare the modes of adaptation of public and private secondary teachers, their acceptance values and facilitative characteristics; and to analyze the intercorrelations of the three variables used.
Thesis (Ed.D.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: Social sciences -- Study and teaching